Whistle stops : adventures in public life - Wyatt, Wilson W. (Wilson Watkins), 1905-1996 (University Press of Kentucky, 1985)
Wilson Wyatt was Jack Kennedy's presidential emissary to Sukarno in a crisis that might have cost the West the oil of the East Indies and lost Indonesia to the Communist orbit. He headed a mission to North Africa during World War II, managed Adlai Stevenson's presidential campaign, and played varied roles on stage and behind the scenes at seven Democratic conventions. He helped guide Kentucky's quiet governmental revolution in the Combs-Wyatt administration, served as wartime mayor of Louisville, launched the nation's postwar housing program under Harry Truman, and today is a leader in Louisvi.